A systematic review of the literature on digital transformation: insights and implications for strategy and organizational change - Hanelt, André (2021)
In this article we provide a systematic review of the extensive yet diverse and fragmented literature on digital transformation (DT), with the goal of clarifying boundary conditions to investigate the phenomenon from the perspective of organizational change. On the basis of 279 articles, we provide a multi-dimensional framework synthesizing what is known about DT and discern two important thematical patterns: DT is moving firms to malleable organizational designs that enable continuous adaptation, and this move is embedded in and driven by digital business ecosystems. From these two patterns, we derive four perspectives on the phenomenon of DT: technology impact, compartmentalized adaptation, systemic shift and holistic co-evolution. Linking our findings and interpretations to existing work, we find that the nature of DT is only partially covered by conventional frameworks on organizational change. On the basis of this analysis, we derive a research agenda and provide managerial implications for strategy and organizational change.